Pengaruh Content Marketing Aplikasi Tiktok, Review Product, Dan Persepsi Harga Terhadap Keputusan Pembelian Produk Masker Camille Beauty - Elviani, Sinta; Zed, Etty Zuliawati (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The increasing number of Internet users in Indonesia, now many applications are used to find information, one of which is the Tiktok application. This study aims to analyze how the influence of Tiktok Application Content Marketing, Product Review, and Price Perception on Purchasing Decisions for Camille Beauty Mask Products.  The type of research used in this study is quantitative research. The population in this study are all consumers who have used the Camille Beauty mask. This study uses data analysis methods with validity tests, reliability tests (normality tests, heteroscedasticity tests, multicollinearity tests, autocorrelation tests), multiple linear regression analysis, t tests, f tests. The results of this study are (1) The content marketing variable has a significant influence on purchasing decisions for Camille Beauty mask products. (2) The product review variable has a significant influence on purchasing decisions for Camille Beauty mask products. (3) The price perception variable has a significant influence on purchasing decisions for Camille Beauty mask products.